Concentrations of Plasma Nucleosomes but Not Cell-Free DNA Are Prognostic in Dogs Following Trauma - Letendre, Jo-Annie; Goggs, Robert (Frontiers in Veterinary Science, 2018)
Trauma is common in dogs and causes significant morbidity and mortality, but it remains a challenge to assess prognosis in these patients. This study aimed to investigate the use of plasma cell-free DNA (cfDNA) and nucleosome concentrations as prognostic biomarkers in canine trauma. Using a prospective, observational case-control study design, 49 dogs with trauma were consecutively enrolled from 07/2015 to 10/2017 and followed to hospital discharge. Dogs with animal trauma triage (ATT) scores ≥3 at presentation were eligible for enrollment. Dogs <3 kg or with pre-existing coagulopathies were excluded. Thirty-three healthy control dogs were also enrolled. Illness and injury severity scores were calculated using at-presentation data. Plasma cfDNA was measured in triplicate using a benchtop fluorimeter. Plasma nucleosome concentrations were determined in duplicate by ELISA. Mann-Whitney U tests were used to compare biomarker concentrations between groups and between survivors and non-survivors. Associations between biomarkers were evaluated using Spearman's correlation coefficients. Alpha was set at 0.05. Concentrations of cfDNA and nucleosomes were significantly higher in injured dogs compared to healthy controls (P ≤ 0.0001). Nucleosomes and cfDNA concentrations were positively correlated (rs 0.475, P < 0.001). Concentrations of both cfDNA and nucleosomes were correlated with shock index (rs 0.367, P = 0.010, rs 0.358, P = 0.012 respectively), but only nucleosomes were correlated with ATT (rs 0.327, P = 0.022) and acute patient physiology and laboratory evaluation (APPLE) scores (rs 0.356, P = 0.012). Median nucleosome concentrations were significantly higher in non-survivors than in survivors [8.2 AU (3.1–26.4) vs. 1.6 AU (0.5–5.2); P = 0.01]. Among illness severity scores, only APPLE was discriminant for survival (AUROC 0.912, P < 0.001). In summary, in moderately-severely injured dogs, high nucleosome concentrations are significantly associated with non-survival.